Властивості ансамблів наночастинок магнетиту у складі магнітних рідин для застосування в онкотерапії - Abramov, N. V.; Gorbyk, P. P. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2012)
The theory of magnetization curves of ferromagnets used to describe the magnetic properties of ferromagnetic nanoparticles synthesized ensembles Fe3O4, and nanocomposites and magnetic fluids on them. Nanocomposites are the structure of the core-shell modifier and contained on the surface of Fe3O4 and drugs: cis-platinum chemotherapy agents and doksirubitsin. Magnetic fluids are made on the basis of these nanocomposites and water or saline. It is shown that the theoretical approaches considered satisfactory description of the magnetic properties of the systems. The magnetic measurements determined with high accuracy dimensional parameters of the synthesized particle ensembles, which are in good agreement with the results of independent researchers. The results will be useful in the practical use of magnetic nanocomposites and fluids in cancer therapy.